A configuração do trabalho docente na educação superior a distância: uma análise do trabalho do tutor - Mariana Novais Vieira (2019)
The theme of this thesis regards the work performed in teaching in higher education in the scope of e-learning. The objective of this study is to understand and analyze the configuration of the tutor's work in the undergraduate distance courses of federal public institutions, regarding the social relations that permeate concrete reality and educational policies in a specific way. The guiding questions of this study are as follows: How is the work of a teacher, specifically the tutor, configured in the undergraduate distance courses of federal public institutions? Has the work in e-learning caused any kind of change in the configuration and dynamics of the work of a teacher? Under what conditions does the tutor's work develop in the context of e-learning? In order to do that, a theoretical descriptive-analytical study guided by historical materialism was carried out based on a literature review and documentary analysis. The following methodological procedures were used: (i) theoretical study, so as to draw a basis for understanding the work of the tutor and e-learning in capitalist social relations; (ii) a documentary study of higher education policies implemented from 1990 to 2016 at the federal level; (iii) analysis of experiences in higher education, both in the national and international levels, focusing on the work of tutors; (iv) problematization and critical analysis of the work of tutors in federal public institutions, based on the information collected, aiming to propose new possibilities for that work. Based on the study carried out, it was possible to conclude that the public higher education teaching work, in terms of e-learning, is being reconfigured, boosting new ways of labor exploitation and deterioration, especially when it comes to the work of tutors, being in line with the assumptions in the model of management status, made public since the 1990s. With the increase of e-learning, the indispensable figure of a new professional emerges: the tutor, who despite exercising a function inherent to teaching, they aren't legally recognized as teachers or workers, acting as a scholar in the federal public sphere, which demarcates a new form of exploitation, deteriorating and outsourcing of teaching work. In this scenario, e-learning must be institutionalized as an educational policy of the State, with the legal incorporation of the tutor as a teaching worker.